Azerbaijan's Strategy to Win the Conflict over the Nagorno-Karabakh Territory with Armenia in 2020 - Maretha Syawallin Umarach; Ali Muhammad (Journal of Islamic World and Politics, 2023)
Decades ago, Armenia and Azerbaijan, two countries in the South Caucasus region, had disagreements over a territorial dispute called Nagorno-Karabakh. In 1921, the Government of the Soviet Union annexed the predominantly ethnic Armenian Nagorno-Karabakh into Azerbaijan. However, after the Soviet Union collapsed in 1991, Armenian separatists seized Nagorno-Karabakh in an incident backed by the Armenian Government. Azerbaijan showed its distaste for this treatment, resulting in fighting between Azerbaijan and Armenia, where around 30,000 people died. Before 2020, the Nagorno-Karabakh conflict could be frozen due to strenuous peace efforts even though various parties had intervened to find the best solution. Until November 10, 2020, Azerbaijani President Ilham Aliyev, Armenian Prime Minister Nikol Pashinyan, and Russian President Vladimir Putin agreed to sign an agreement to stop the fighting that had been taking place in the Nagorno-Karabakh region. The ceasefire was signed after Azerbaijani military forces managed to control most of Nagorno-Karabakh. This study uses an offensive realism paradigm to analyze Azerbaijan's strategy to win the conflict over the Nagorno-Karabakh region with Armenia in 2020. The results revealed that Azerbaijan developed beneficial diplomatic relations with Turkey, Israel and Russia. These countries later assisted. One of them was the assistance of military equipment which enabled Azerbaijan to win the war against Armenia.